Probe-molecule-assisted NMR spectroscopy: A comparison with photoluminescence and electron paramagnetic resonance spectroscopy as a characterization tool in facet-specific photocatalysis - Peng, Y; Fu, Y; Zhang, L; Teixeira, I; Ye, L; He, H; Tsang, S (Wiley, 2016)
Photoluminescence (PL) and EPR spectroscopy are the two most commonly used techniques to evaluate surface oxygen vacancies (V O surface ) on photoactive transition metal oxides. However, these techniques have shortcomings in the characterization of facet-dependent catalysis. Here, we used the chemical adsorption of a 31 P-containing probe molecule to obtain the distribution/concentration of V O surface as well as other surface features (hydroxyl groups) of ZnO by using 31 P magic-angle spinning NMR spectroscopy. This facet-specific technique not only makes cross-literature comparison feasible but also provides more comprehensive information to lead to a further understanding of the photocatalytic mechanism.